Implementasi Algoritma Linear Congruent Method Pada Aplikasi Belajar Mandiri Siswa - Ibadi, Taqrim; Krisulta, Rudi (Jurnal Ilmiah Matrik, 2024)
Abstract : This research aims to implement the Linear Congruent Method (LCM) algorithm in the application of student self-learning in the INET Computer Course Institute. The LCM algorithm is used to generate random numbers required in learning features, such as practice questions and random tests. This study evaluates the effectiveness of the algorithm in improving the quality of self-learning through applications. The research method involves application development, and algorithm integration. The results of the study show that the implementation of the LCM Algorithm has succeeded in improving the variety and quality of the learning content presented. The app has proven to be efficient in providing random materials, which supports student interaction and improves their understanding of the material. This research contributes to the development of more effective and adaptive educational applications, as well as opens up opportunities for further research in the field of educational algorithms and technology.